The Position of Maqasid al-Shariahwithin Islamic Legal Sources:A Comprehensive Analysis - Muhammad Nazir Alias; Muhammad Najib Abdullah; Mohd Farihal Osman; Nor Faizah Ismail; Mohd Sham Kamis (Universitas Islam Negeri Ar-Raniry, 2025)
Indexed